2010
DOI: 10.1002/nau.20975
|View full text |Cite
|
Sign up to set email alerts
|

Secondary changes in bowel function after successful treatment of voiding symptoms with neuromodulation

Abstract: Studies have indicated that neuromodulation improves FI in carefully selected patients. The impact on other bowel conditions, including IBS, is unclear. Since voiding and bowel symptoms often coexist, it is crucial to fully evaluate all potential treatment benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…One retrospective study [2] with long-term follow-up noted a 58.6% rate of bowel complaints in a mixed male and female population with varying urologic conditions, including urinary urgency and frequency, UUI, and urinary retention. This is similar to the overall 64.3% prevalence in the recent, comprehensive, prospective study [21] mentioned previously. However, further review of the literature, including other recent publications [19,20] on concomitant benefits of SNS on bowel function, revealed no estimates of the prevalence of concurrent bowel dysfunction in refractory UUI.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…One retrospective study [2] with long-term follow-up noted a 58.6% rate of bowel complaints in a mixed male and female population with varying urologic conditions, including urinary urgency and frequency, UUI, and urinary retention. This is similar to the overall 64.3% prevalence in the recent, comprehensive, prospective study [21] mentioned previously. However, further review of the literature, including other recent publications [19,20] on concomitant benefits of SNS on bowel function, revealed no estimates of the prevalence of concurrent bowel dysfunction in refractory UUI.…”
Section: Discussionsupporting
confidence: 91%
“…A large study [6] of the prevalence of anal incontinence with urinary incontinence and pelvic organ prolapse found that in women without prolapse, 24% with unspecified urinary incontinence had anal incontinence, and more specifically, 29% with detrusor instability had anal incontinence. This is notably lower than the 80% rate of FI in a sample of men and women with urinary urgency/frequency with or without UUI, as described in a recent prospective study [21] investigating bowel dysfunction with all urologic SNS indications. The 83% prevalence of fecal incontinence with UUI observed in the current study agrees with this latter observation, likely due to a more severe pathology existing in refractory UUI patients receiving SNS.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations